Genotype × Environment Interaction Studies of Promising Teppi Coffee (Coffea arabica L.) Genotypes in Southwestern Ethiopia. (12th May 2021) - Merga, Wakuma; Gebreselassie, Wosene; Garedew, Weyessa
Abstract : Coffee is the stimulant crop plant that belongs to the genus Coffea, in the family Rubiaceae. The yield variation and pattern of the crop varied within short geographic distance and thus attributed to low productivity and unpredictable production. The objective of this study was to determine the extent of genotype × environment interaction on yields of promising Teppi coffee genotype. In this study, seventeen Arabica coffee genotypes, representing coffee growing areas of Teppi, southwestern Ethiopia were evaluated at six environments. This study was conducted by using completely randomized block design with two replications. The extent of genotype × environment interaction was analyzed by using additive main effect and multiplicative interaction model and genotype main effect and genotype × environment interaction biplot analysis model. The analysis of variance for yield revealed the presence of highly significant differences (P < 0.01 ) within genotypes, environments and genotype by environment interaction. From the total sum of squares of genotype × environment interaction of yield, environment accounted for 51% while genotypic and GEI effects were 20.5% and 25.32%, respectively. Generally, genotypes with superior performance and suitable environments for coffee were identified. However, further researches have to target hybridization of those superior genotypes with elite lines in feature Arabica coffee breeding program.